PENGEMBANGAN PRODUK CASING ALAT KESEHATAN PEMANTAUAN INFUS PINTAR (MIFUS) DENGAN METODE RAPID TOOLING - Media, Riona Ihsan; Kusnowo, Roni; Hendrawan, Yogi Muldani; Musa, Hafez Trimukti Ali (Jurnal Rekayasa Mesin, 2024)
MiFUS® is a tool that can display the patient's infusion condition so that nurses can monitor patients one by one in a short time simultaneously. Several nurses were involved in this study to provide input to the casing. Product design is done at the beginning to know the initial casing design. Next, the manufacture of casing molds is carried out using a 3D printing machine. The results of the 3D printer are used as a Master Mold for the implementation of Rapid Tooling method with Epoxy material. The solution of product development is catalyst ratio analysis on polyester resin to obtain the optimal ratio of properties including shrinkage and strength of the material to withstand mechanical loads. Validation of shrinkage is carried out using 3D Scanning technology to determine the deviation of dimensions in the casing made against CAD data. Meanwhile, to obtain the strength parameters of the material to withstand mechanical loads, tensile testing is carried out. The results of this study are the contribution of design parameters, namely the amount of shrinkage that occurs and the strength parameters of the material to withstand mechanical loads. The Data and information are presented in the form of product prototypes and user analysis feasibility studies.